Project Based Learning in Physics Learning Material to Form Students' Islamic Character: A Systematic Literature Review - Yuyung, Andi (ETDC: Indonesian Journal of Research and Educational Review, 2025)
Physics learning on Newton's Laws often focuses only on the cognitive aspect, thus under-emphasizing the character and spiritual values of students. In fact, a comprehensive education should foster students holistically, encompassing intellectual, social, and religious aspects. This study intends to systematically examine the application of Project Based Learning (PjBL) in physics learning as a pedagogical strategy that not only improves students' understanding of Newton's Laws but also shapes their Islamic character. This study uses a systematic literature review method with the PRISMA approach, which involves the identification, screening, eligibility, and inclusion of 125 articles from various databases (Google Scholar, DOAJ, Scopus, etc.), until 30 relevant articles from the last 10 years are selected. The results of the study indicate that PjBL can improve students' conceptual understanding through contextual and collaborative project activities. In addition, PjBL is also effective in fostering character values such as responsibility, cooperation, and honesty, and it can be integrated with Islamic values through a thematic and reflective approach. In conclusion, the application of PjBL in physics learning improves students' cognitive quality and serves as an effective means of forming Islamic character. This study recommends the development of teaching tools that explicitly integrate PjBL with Islamic values.